Quenching of ketone triplet excited states by atmospheric halides. Issue 1 (23rd December 2020) - Gemayel, R.; Emmelin, C.; Perrier, S.; Tomaz, S.; Baboomian, V. J.; Fishman, D. A.; Nizkorodov, S. A.; Dumas, S.; George, C.
Abstract : The photosensitized chemistry of three aromatic ketones (xanthone, flavone, and acetophenone) and also of secondary organic aerosols (SOAs) arising from the photo-oxidation of naphthalene was investigated by means of transient absorption spectroscopy. Abstract : The photosensitized chemistry of three aromatic ketones (xanthone, flavone, and acetophenone) and also of secondary organic aerosol (SOA) arising from the photo-oxidation of naphthalene was investigated by means of transient absorption spectroscopy. Halide ions were selected to probe the reactivity of the generated triplet states. The quenching rate constants ranged from 10 9 M −1 s −1 with iodide ions to less than 10 5 M −1 s −1 with chloride ions. The halide-triplet state interactions produced the corresponding radical anion (X2 ˙ − ) along with halogenated and more oxidized organic compounds as identified by liquid chromatography and mass spectrometry. Deoxygenated naphthalene SOA solutions showed strong transient absorption at 420 nm when excited at 355 nm, and were also quenched by iodide ions similar to the single compound experiments indicating that compounds in naphthalene SOA can act as photosensitizers. Combining the study of these individual and known photosensitizers with those formed in the atmosphere (in this case through the oxidation of naphthalene) demonstrates that tropospheric photosensitization may involve a large variety of compounds of primary or secondary nature and will introduce new, unconsidered chemical pathways that impact atmospheric multiphase chemistry.